Diagnostic accuracy and safety of Diaskintest® compared with the tuberculin skin test for detecting tuberculosis infection in BCG-vaccinated Brazilian adults - Kritski, Afrânio; Conceição, Carla; Oliveira, Martha; Dalvi, Ana Paula Razal; Cordeiro-Santos, Marcelo; Moreira, Adriana Rezende; Lopes, Aline; Ruffino, Rogerio; Rodrigues, Luciana; Mesquita, Eliene; Cardozo, Sergian Vianna; Pereira, Maria Jose Fernandes; et al. (Frontiers in Medicine, 2026)
BackgroundEvidence on the accuracy and safety of the ESAT-6/CFP-10–based Diaskintest® in BCG-vaccinated populations outside Eastern Europe remains limited. In Brazil, recurrent shortages of purified protein derivative (PPD) have challenged the implementation of tuberculin skin testing, underscoring the need to evaluate alternative tools for tuberculosis infection (TBI) screening. This trial compared the diagnostic performance and safety of Diaskintest® with the tuberculin skin test (TST) using PPD Rt-23 in Brazilian adults, a predominantly BCG-vaccinated population.MethodA double-blind randomized clinical trial was conducted at eight centers in Brazil between July 2023 and September 2024. Participants were allocated to the TB group (microbiologically confirmed pulmonary TB), in whom sensitivity was estimated, and the control group (healthy, unexposed adults), in whom specificity was estimated using the QuantiFERON-TB Plus® (QFT-Plus) as the reference standard. All participants first underwent QFT-Plus testing, followed by intradermal application of Diaskintest® and TST in opposite arms, with randomized right–left allocation. Induration was measured at 48–96 h using a prespecified 5 mm cutoff. Secondary outcomes included safety, assessed through active monitoring of adverse events (AEs), included injection site reactions.ResultsA total of 337 controls and 136 TB participants were enrolled. TST showed higher sensitivity than both Diaskintest and QFT-plus (0.84 [95% CI 0.76–0.90] vs. 0.68 [95% CI 0.59–0.76], and 0.63 [95% CI 0.54–0.72], respectively). Diaskintest® demonstrated higher specificity than TST (0.93 [95% CI 0.90–0.96] vs. 0.75 [95% CI 0.70–0.80]). Injection-site reactions occurred less frequently with Diaskintest® than with TST (1.7% vs. 4.9%. RR = 0.35 [0.15–0.79]). The most common reactions were phlyctenular reactions and itching. No serious AEs were observed.ConclusionTST had greater sensitivity than Diaskintest®, whereas Diaskintest® demonstrated higher specificity and fewer local adverse reactions. In this study, specificity was estimated using QFT-Plus as a surrogate reference standard, acknowledging the absence of a true gold standard for tuberculosis infection. These complementary performance profiles highlight a trade-off between false-positive reduction and case detection, suggesting that the choice of test should consider programmatic priorities and local epidemiological context.Clinical trial registrationhttps://ensaiosclinicos.gov.br/, identifier RBR-7tn2ysw.